On weak convergence of the sums of multidimensional stochastic point processes - Grigelionis, B. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Григелионис. О слабой сходимости сумм многомерных случайных точечных процессовB. Grigelionis. Apie daugiamačių atsitiktinių taškinių procesų sumų silpną konvergenciją